Semangat Feminisme Dalam Pengalaman Spiritual Rabi'ah Al-'Adawiyah - Affan, Mohammad (Sunan Kalijaga State Islamic University & The Asia Foundation, 2008)
Sufism (tasawwuf) states strongly the equity of human beings: men and women. Existinggender differences do not hinder the spiritual achievement of men and women because spirituality connotes universal meaning free from any particular gender identity. Spirituality concerns eternal life and values, whereas gender identity is a profane affairs and consituting a wordly life. In this light, although men and women assume different gender role in their worldly life, both of them have same potency to achieve the highest spiritual experience and gain ascetic happiness. Sufis doctrine celebrates oneness without any individuality. The history of sufism witnessed the effifacy of women to the top highest state of spirituality. Rabi'ah Al-Adawiyah was the phenomenal example of one who initiated the concept of mahabbatullah in its holistic meaning. Through her concept of hubb (love) Rabi'ah reached the highest spiritual maqam (state) in sufis ranks, higher than other sufis could reach at her time. The achievement of Rabi'ah to the ultimate stage of spirituality through her notion of mahabbah is a clear and firrn proof that spirituality never requires particular gender identity; both women and men have equal potency and opportunity to attain or experience such ultimate encounter with spirituality.